Effects of Human Umbilical Cord-Derived Mesenchymal Stem Cells on the Acute Cigarette Smoke-Induced Pulmonary Inflammation Model - Chen, Xiao-Yue; Chen, Yi-Ying; Lin, Willie; Chien, Chia-Wen; Chen, Chien-Han; Wen, Yu-Chieh; Hsiao, Ta-Chih; Chuang, Hsiao-Chi (Frontiers in Physiology, 2020)
Cigarette smoke (CS) has been reported to induce oxidative stress and inflammatory process in the lungs. However, the role of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) in the regulation of pulmonary inflammation remains unclear. The objective of this study is to investigate the effects of hUC-MSCs on lung inflammation in the acute CS-induced pulmonary inflammation animal model. Eight-week-old male C57BL/6 mice were intravenously administered 3 × 106, 1 × 107, and 3 × 107 cells/kg of hUC-MSCs as well as normal saline alone (control) after 3 days of CS exposure. Mice exposed to high-efficiency particulate air (HEPA)-filtered room air served as the CS control group. High -dose (3 × 107) hUC-MSC administration significantly decreased tumor necrosis factor (TNF)-α in the bronchoalveolar lavage fluid (BALF) of CS-exposed mice (p < 0.05). The chemokine (CXC motif) ligand 1/keratinocyte chemoattractant (CXCL1/KC) in BALF were significantly reduced by low-dose (3 × 106) and high-dose (3 × 107) hUC-MSC (p < 0.05). Medium-dose hUC-MSC administration decreased interleukin (IL)-1β in lung of mice, and TNF-α and caspase-3 were decreased in the lung of CS-exposed mice by medium and high-dose MSC (p < 0.05). Low-dose hUC-MSCs significantly elevated serum CXCL1/KC and IL-1β in CS-exposed mice (p < 0.05). Our results suggest that high-dose hUC-MSCs reduced pulmonary inflammation and had antiapoptotic effects in acute pulmonary inflammation.